2000
DOI: 10.1007/s001340000653
|View full text |Cite
|
Sign up to set email alerts
|

The initial distribution volume of glucose rather than indocyanine green derived plasma volume is correlated with cardiac output following major surgery

Abstract: Our results indicate that IDVG rather than intravascular volume is correlated with cardiac output. We suggest that IDVG has potential as an alternative indicator of cardiac preload following major surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 30 publications
1
20
0
Order By: Relevance
“…IDVG was correlated well with CO during and after subsequent fl uid volume loading in our experimental studies [1,2]. Additionally, IDVG rather than plasma volume, or blood volume, displays a better correlation with CO after major abdominal surgery, suggesting that IDVG has potential as an indicator of cardiac preload [10], even though glucose administered intravenously cannot stay in the intravascular compartment and is rapidly distributed into the extravascular space; thus, the concept of dilution volumetry is different from "true" cardiac preload.…”
Section: Discussionmentioning
confidence: 71%
“…IDVG was correlated well with CO during and after subsequent fl uid volume loading in our experimental studies [1,2]. Additionally, IDVG rather than plasma volume, or blood volume, displays a better correlation with CO after major abdominal surgery, suggesting that IDVG has potential as an indicator of cardiac preload [10], even though glucose administered intravenously cannot stay in the intravascular compartment and is rapidly distributed into the extravascular space; thus, the concept of dilution volumetry is different from "true" cardiac preload.…”
Section: Discussionmentioning
confidence: 71%
“…The initial distribution volume of glucose (IDVG), representing central extracellular fluid (ECF) volume, is another tool for assessment of cardiac preload. Some studies indicated IDVG had closer correlation with cardiac output (CO) than plasma volume determined by the indocyanine green dilution method [2], and this method has been successfully used for prediction of postoperative hypovolemia [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…We previously proposed initial distribution volume of glucose (IDVG), determined using injection of a small amount of glucose (5 g), as a measure of central extracellular fluid volume status [1-3]. Neither the plasma glucose values present before glucose injection nor infusion of insulin and/or vasoactive drugs had any apparent effect on IDVG calculation [1-3].…”
Section: Introductionmentioning
confidence: 99%
“…Neither the plasma glucose values present before glucose injection nor infusion of insulin and/or vasoactive drugs had any apparent effect on IDVG calculation [1-3]. IDVG has been demonstrated to correlate well with cardiac output in various critically ill conditions in the absence of congestive heart failure [1,4].…”
Section: Introductionmentioning
confidence: 99%